Regional Differences in Lumbar Vertebrae Morphometry: A CT Study Comparing North and South Indian Populations - Neha Gaur; Dr Satyam Khare; Dr Shilpi Jain; Dr Mahesh Kumar Mittal; Dr Avinash Rastogi (The Bioscan, 2026)
Background: Lumbar vertebral morphometry varies with ethnicity and has important implications for spinal diagnosis and instrumentation. Data comparing North and South Indian populations remain limited. Objective: To evaluate and compare CT-based morphometric parameters of lumbar vertebrae (L1–L5) between North and South Indian adults and assess their clinical relevance for transpedicular fixation. Materials and Methods: A cross-sectional CT-based study was conducted on 1,000 adults (500 North Indian, 500 South Indian) aged 18–50 years. Thin-slice (1 mm) multidetector CT images were analyzed to measure vertebral body dimensions, pedicle parameters, canal dimensions, and angular indices at L1–L5. Statistical comparisons were performed using t-tests, ANOVA, and Pearson correlation, with p < 0.05 considered significant. Results: Significant regional differences were observed across most lumbar parameters (p < 0.001). North Indians consistently demonstrated greater vertebral body heights, anteroposterior diameters, sagittal depths, and vertebral areas, indicating larger and taller vertebral bodies. South Indians showed significantly higher pedicle-related and transverse parameters, including pedicle width, interpedicular distance, and transverse pedicle angle, suggesting wider pedicles and spinal canals. These patterns were consistent across lumbar levels and both sexes, with a few level-specific non-significant variables. Conclusion: Marked North–South Indian differences exist in lumbar vertebral morphometry. These findings highlight the necessity of population-specific anatomical data for optimal pedicle screw sizing, safer spinal instrumentation, and improved clinical outcomes in Indian patients. Keywords Lumbar vertebrae; Vertebral morphometry; Computed tomography; North Indian population; South Indian population; Pedicle screw fixation